Uji Efikasi Rodentisida Nabati Daun Ruku-ruku (Ocimum sanctum L.) terhadap Mortalitas Tikus Sawah (Rattus argentiventer Robb & Kloss) di Laboratorium - Christine Nofriaeti Lusiana Sinaga; Maryani Cyccu Tobing; Mukhtar Iskandar Pinem (Universitas Sumatera Utara, 2017)
ABSTRACTThe objective of this research was to study the efficacy of botanical pesticide Ocimum sanctum leaves on rice field rat mortality in laboratory. This research was conducted in Laboratory of Vertebrate Pest Control Balai Besar Perbenihan dan Proteksi Tanaman Perkebunan (BP2TP), Medan (± 25 m asl) from December 2015 until February 2016.The method used Randomized Complete Design non Factorial with three replications. The results showed that O. sanctum leaves affected reduction in body weight of Rattus argentiventer. The highest bait consumption was showed on 60% O.sanctum in bait (19.33 g) and the lowest control (13.67 g) on first day after application. The highest 60% O. sanctum in bait mortality percentage (16.67%) and the lowest was showed on control (0.00%) on day eighteen after application. Behaviour of rats rest (46.64%), shiver (15.06%), along the floor (13.87%), bitting cage (8.39%), bitting food/water box (6.75%), repeat salto (5.79%), lack of appetite (1.86%), inactivity (0.98%), and bleeding on eye/nose (0.66%).Keywords: botanical rodenticides, Rattus argentiventer, Ocimum sanctum.